PEMBERIAN ASIMILASI NARAPIDANA RESIDIVIS (STUDI KASUS DI L.P. PEREMPUAN KELAS IIA MALANG) (Jurnal Magister Hukum Perspektif, 2020)
The policy of assimilation of prisoners in the midst of the COVID-19 pandemic, namely the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration for Prisoners and Children in the Framework of Prevention and Countermeasures of the Spread of COVID-19 is very interesting to be further peeled. The policy received a lot of support as well as criticism from many parties. Many people worry about the repetition of crimes committed by ex-assimilation prisoners. Based on the background above, the author raised the formulation of the problem as follows: "How is the legal politics of Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 against recidivist prisoners in Malang Class IIA Women's Prison?" The method used in this writing is an empirical juridical method with a sociological approach that seeks to describe the implementation Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 in people's lives. Primary data collection is done by interview while secondary data is obtained from library studies and documents related to research problems. The results of the review explained that the strategy for handling prisoners who commit crimes again after being released through the assimilation program at home carried out at the Malang Class IIA Women's Prison is in accordance with Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration Rights for Prisoners and Children in the Framework of Prevention and Countermeasures of the Spread of COVID-19. The legal politics applied to keep recidivism rates low are to impose more severe sanctions on inmates and children who repeat their crimes. In the Women's Penitentiery Class IIA Malang, there are 1 (one) recidivist prisoner who is free of COVID assimilation and is currently locked in a straft cell at women’s penitentiery Class IIA Malang. Keywords: Legal Politics, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020, Recidivist